(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
This article scientifically and practically analyzes passive safety systems that ensure child safety in modern vehicles. Passive safety systems are systems designed to minimize injuries to passengers after a road traffic accident occurs, and they are of particular importance for children. The research results show that adapting passive safety systems to the anatomical and physiological characteristics of children can significantly reduce child injuries and fatalities in road traffic accidents.